DETEKSI PENYAKIT TIDAK MENULAR DAN UPAYA PENCEGAHAN PADA WARGA KELURAHAN SONDAKAN LAWEYAN SURAKARTA - Darah Ifalahma; Nur Hikmah; Ana Yuliana; Septi Wulandari; Herni Safitri (LPPM Universitas Bina Bangsa, 2023)
The human lifestyle due to urbanization, modernization and globalization is one of the causes for the increase in Non-Communicable Diseases. In general, Non-Communicable Diseases such as obesity, Diabetes Mellitus and hypertension are one of the main causes of death globally. Hypertension is a very dangerous non-communicable disease (Silent Killer). Based on data from the World Health Organization (WHO), worldwide around 972 million people or 26.4% of the world's inhabitants suffer from hypertension. In Indonesia, the prevalence of hypertension reaches 31.7% and around 60% of people with hypertension end in stroke. Factors that cause hypertension are genetic factors and environmental factors such as obesity, stress, excessive salt consumption, smoking, and alcohol. Diabetes Mellitus is the sixth leading cause of death in the world. In Indonesia the prevalence of Diabetes Mellitus is around 4.8%. From the results of data collection regarding the PISPK data collection in the Pajang Health Center area in RW 10 Sondakan Laweyan Surakarta, it was found that the community had problems with hypertension and diabetes mellitus. The purpose of this activity is to detect non-communicable diseases and their prevention as well as improve the health status of Sondakan Village residents. The implementation method is carried out using a physical examination method in the form of a blood pressure health check and blood sugar check. Furthermore, with the educational method by providing health education to 58 residents. This method is carried out with 5 (five) main activity plans, namely preparation, socialization, implementation, evaluation and termination. Service activities prioritize early detection of non-communicable diseases, namely hypertension and diabetes mellitus. This program is carried out using physical examination and educational methods as an effort to prevent hypertension and diabetes mellitus. The result of this activity is that there are several residents of RW 10 Sondakan Village who have hypertension and diabetes mellitus. Residents already understand about non-communicable diseases and are willing to pay attention to healthy living behavior as a form of prevention efforts, residents are willing to carry out routine health checks at health facilities and health services which are carried out every month at the puskesmas